Exploração do corpo em movimento aplicando várias formas e técnicas de expressão - Pessanha, Ana Maria, 1957- (2019)
This work entitled “Exploration of the Body in Motion applying various forms and techniques of expression”, is integrated at the Vergilio Ferreira Group of Schools within the scope of the Project “European Year of Cultural Heritage”, held in the academic year 2017/2018. It is proposed to a group of 25 students aged between 4 and 6 years of Kindergarten on the Basic School of Lumiar in the scope of teacher training.Situations of expressive exploration were developed: investigation, discovery and observation of works of artists: works of Leonard of the Vinci Matisse Henri; Lourdes Castro; Amadeu Sousa Cardoso; Visit to an exhibition and the studio of an artist. The group of chil have developed various activities of exploration and discovery of their body applying several Forms and Techniques of Expression